Dr. Stefan Luchian — Deep Plane Facelift — Paris - Luchian, Stefan (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Stefan Luchian, practicing in Paris, France. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003210; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; france; paris